2008
DOI: 10.1260/174795408785100635
|View full text |Cite
|
Sign up to set email alerts
|

Servant Leadership in Sport: A New Paradigm for Effective Coach Behavior

Abstract: Coaches are searching for contemporary leadership models which resonate with the modern-day athlete. Many elements of the Servant Leadership model, such as trust, inclusion, humility and service, are well suited to enhanced coach behaviors with this cohort. The purpose of this study was to examine how coaches who were perceived by their athletes to possess “servant leader” characteristics were associated with their athletes' use of mental skills, motivation, satisfaction and performance Participants were 195 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 10 publications
2
56
0
1
Order By: Relevance
“…Both Rowold [15] and Callow et al [16] have tested the applicability of the transformational leadership model [17] to the sport coaching context with positive results, and have been supported by qualitative work [18]. Extending this, research has recently suggested that servant leadership may also be an appropriate model [19]. Servant leadership is defined by the core constructs of trust, humility and service to others.…”
Section: Review Of the Current Models Leadership Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both Rowold [15] and Callow et al [16] have tested the applicability of the transformational leadership model [17] to the sport coaching context with positive results, and have been supported by qualitative work [18]. Extending this, research has recently suggested that servant leadership may also be an appropriate model [19]. Servant leadership is defined by the core constructs of trust, humility and service to others.…”
Section: Review Of the Current Models Leadership Modelsmentioning
confidence: 99%
“…Chelladurai must also be applauded for the integration of aspects of the transformational leadership model into his multidimensional model [28]. Moreover, recent studies have recommended various leadership styles as the most suitable for sports coaching, including transformational leadership [15][16], servant leadership [19] and altruistic leadership [20]. Notwithstanding this recent influx of relational additions to the literature, the definition of coach leadership as a purely behavioural process may only serve to slow the progress on the understanding of coach leadership as it unfolds in the reality of coaching practice.…”
Section: The Current Definition Of Coach Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of building and managing healthy relationships in secular sport coaching and physical education texts has received some attention (e.g., Martens, 2004). Nonetheless, with a handful of exceptions (Rieke, Hammermeister and Chase, 2008;Fellowship of Christian Athletes, 2008;Gallagher, 2008;Dungy, 2008;Wooden, 2005 xxxv ;McCown and Gin, 2003;Boyers, 2000) there has been very limited Christian reflection on relationships on able-bodied sport and certainly not for disabled sport. 113) found in her study of the use of leisure and sport in L'Arche, leisure can be used to foster community and 'the Christian focus of love in L'Arche is to announce the ridiculous-that we NEED them to teach us to trust, laugh easily, live more in the moment, enjoy the presence of others, and accept one another unconditionally'.…”
Section: Timothy Shriver Ceo Special Olympics (2010a: 6)mentioning
confidence: 99%